2008
DOI: 10.1007/s00417-008-1013-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anterior corneal asphericity and refractive variables

Abstract: Q-values varied according to the refractive properties examined. However, the relationship between refractive state and corneal asphericity was found to be determined more by the geometric properties of the eye (corneal power and axial length) than by manifest refraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 25 publications
5
22
1
Order By: Relevance
“…As stated, this relationship between corneal geometry and anatomic parameters may be related to the optical and refractive status of the eye. 30 Nieto-Bona et al 30 found that Q values varied in a sample of 118 normal eyes and that the variability was dependent on the refractive properties of the eye. These same authors found a trend toward more negative Q-values with increasing corneal diameter, which is consistent with the trends for the anterior:posterior ratio for corneal shape factor in our series.…”
Section: Discussionmentioning
confidence: 99%
“…As stated, this relationship between corneal geometry and anatomic parameters may be related to the optical and refractive status of the eye. 30 Nieto-Bona et al 30 found that Q values varied in a sample of 118 normal eyes and that the variability was dependent on the refractive properties of the eye. These same authors found a trend toward more negative Q-values with increasing corneal diameter, which is consistent with the trends for the anterior:posterior ratio for corneal shape factor in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Lam and Loran 7 reported differences in some corneal parameters (that is, horizontal visible iris diameter (HVID), corneal curvature) between Chinese and Caucasian populations. Most of the studies evaluating anterior corneal shape were performed on adults, 8–14 with only a few publications reporting the corneal shape of children 15–18 …”
mentioning
confidence: 99%
“…4) have shown repeatedly that there are meridional variations in corneal shape. Recently, Nieto-Bona et al 41 have shown that classifying their subjects according to their magnitude of corneal astigmatism, but not their M or corneal powers, led to significantly different corneal shapes. Taken together, these results indicate the significance of astigmatic components when interpreting corneal shape parameters.…”
Section: Discussionmentioning
confidence: 98%
“…In this respect, previous studies have reported mixed effects of refractive error on the corneal shape: some studies found a less prolate/more oblate corneal shape with myopia progression 49,50 or increased magnitudes of myopia, 43 but other studies either found a more prolate corneal shape with increased myopia 42 or failed to find a significant difference in corneal asphericity across emmetropes, hyperopes, and myopes. 41 One possibility for the discrepancies found across different studies could be caused by the different experimental designs, including the age range involved, the classifications of refractive errors, and the diameter used to calculate the corneal shape factors. It is also possible that the coexistence of astigmatism with myopia and hyperopia 3,5,51 has confounded the effects of refractive errors on corneal shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation